Animal experimental models of ischemic limbs - A systematic review - Lovasova, Veronika; Bem, Robert; Chlupac, Jaroslav; Dubsky, Michal; Husakova, Jitka; Němcová, Andrea; Fronek, Jiri (Vascular pharmacology, 2023)
BACKGROUND: The objective of this systematic review is to summarize the available animal models of ischemic limbs, and to provide an overview of the advantages and disadvantages of each animal model and individual method of limb ischemia creation. METHODS: A review of literature was conducted using the PubMed and Web of Science pages. Various types of experimental animals and surgical approaches used in creating ischemic limbs were evaluated. Other outcomes of interest were the specific characteristics of the individual experimental animals, and duration of tissue ischemia. RESULTS: The most commonly used experimental animals were mice, followed by rabbits, rats, pigs, miniature pigs, and sheep. Single or double arterial ligation and excision of the entire femoral artery was the most often used method of ischemic limb creation. Other methods comprised single or double arterial electrocoagulation, use of ameroid constrictors, photochemically induced thrombosis, and different types of endovascular methods. The shortest duration of tissue ischemia was 7 days, the longest 90 days. CONCLUSIONS: This review shows that mice are among the most commonly used animals in limb ischemia research. Simple ligation and excision of the femoral artery is the most common method of creating an ischemic limb; nevertheless, it can result in acute rather than chronic ischemia. A two-stage sequential approach and methods using ameroid constrictors or endovascular blinded stent grafts are more suitable for creating a gradual arterial occlusion typically seen in humans. Selecting the right mouse strain or animal with artificially produced diabetes or hyperlipidaemia is crucial in chronic ischemic limb research. Moreover, the observation period following the onset of ischemia should last at least 14 days, preferably 4 weeks.
Keywords: stenty; Sheep; ovce; Humans; Ischemia; Femoral Artery; krysa rodu Rattus; lidé; modely u zvířat; zvířata; myši; Mice; Swine; Stents; teoretické modely; ischemie; králíci; Models, Animal; Rats; arteria femoralis; Animals; Models, Theoretical; Disease Models, Animal; Rabbits; prasata; modely nemocí na zvířatech